2D.02: ACCURACY OF ISOVOLUMETRIC CONTRACTION TIME OBTAINED BY CAROTID ARTERIAL TONOMETRY IN PATIENTS WITH CHRONIC LEFT VENTRICULAR FAILURE. (June 2015) - Salvi, L.; Grillo, A.; Marelli, S.; Gao, L.; Giuliano, A.; Trifirò, G.; Santini, F.; Pini, A.; Salvi, P.; Viecca, F.; Carretta, R.; Parati, G.
Abstract : Objective: The Buckberg index (SEVR: subendocardial viability ratio) is considered a useful parameter for a non-invasive assessment of the relationship between subendocardial oxygen supply and demand. However, his classic calculation does not include the pre-ejection isovolumic contraction time in stroke work evaluation. The aim of our study was to evaluate the accuracy of the isovolumic contraction time obtained through the carotid pulse wave analysis, to be included in SEVR assessment. Design and method: In 35 patients (mean age ± SD = 66 ± 13 yrs) followed-up for chronic left ventricular systolic failure (EF = 32 ± 8%) with no significant valvular disease, the pressure curve in the common carotid artery by tonometer (PulsePen) and the aortic transvalvular flow by EchocardioDoppler (Philips-EnVisor C-HD) were acquired simultaneously. The synchronization of data acquisition was verified by comparison of the RR intervals in the ECG signals recorded simultaneously to the two methods. The isovolumic contraction time was separately calculated by considering both the delay between the beginning of the aortic flow wave obtained by EchocardioDoppler and the R wave of the corresponding ECG, and the delay between the foot of the pressure wave recorded in the carotid artery by tonometry compared with the R wave of the corresponding ECG. The latter was corrected by considering the delay between ascending aorta and carotid pulses, computed as a function of the carotid-femoral pulse wave speed and of the distance between the point of carotid pulse acquisition and the sternal notch. Results: The isovolumic contraction time computed by tonometry (68.8 ± 20.2 ms) was closely related to that measured with the EchocardioDoppler approach (68.8 ± 20.5 ms): y = 0.93x + 4.94; r 2 = 0.93; p < 0.0001, with homogeneous distribution in Bland-Altman analysis (mean difference -0.1 ± 7.57 ms). The ratios between isovolumic contraction time and systolic ejection time separately obtained with the two methods (24.8 ± 8.3% and 22.2 ± 8.5%, respectively) were closely related: y = 0.93x + 1.67; r 2 = 0.90 (mean difference -0.1 ± 2.7%). Conclusions: Thus, carotid arterial tonometry allows an accurate and simple assessment of the isovolumic contraction time, which can be employed to improve the assessment of SEVR by also considering the isovolumic contraction time in the stroke work evaluation.